2008
DOI: 10.1016/j.neurobiolaging.2007.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Age-related spatial learning impairment is unrelated to spinophilin immunoreactive spine number and protein levels in rat hippocampus

Abstract: Age-related impairments in hippocampus-dependent learning and memory tasks are not associated with a loss of hippocampal neurons, but may be related to alterations in synaptic integrity. Here we used stereological techniques to estimate spine number in hippocampal subfields using immunostaining for the spine-associated protein, spinophilin, as a marker. Quantification of the immunoreactive profiles was performed using the optical disector/fractionator technique. Aging was associated with a modest increase in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
2
11
1
Order By: Relevance
“…Consistent with previous studies [17], [18], [19], approximately half of the aged subjects displayed deficits relative to young rats, whereas the other half performed within the range of adult controls (Fig. 1A).…”
Section: Resultssupporting
confidence: 91%
“…Consistent with previous studies [17], [18], [19], approximately half of the aged subjects displayed deficits relative to young rats, whereas the other half performed within the range of adult controls (Fig. 1A).…”
Section: Resultssupporting
confidence: 91%
“…Studies of spinophilin were conducted in aging rodents in regions other than associational cortex and produced inconsistent results. For example, Calhoun et al (2008) found no changes in rat hippocampal spinophilin protein with aging, whereas an age-related decrease in spinophilin protein was observed in the striatum (Brown et al, 2005). Our cohort of aged individuals with NCI, MCI, and AD was not optimal for examining an association between age and PreC spinophilin levels, due to a narrow age range (79.0–94.5 years).…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal synapse number seems to be preserved in aged rodents in some regions, and decreased in other regions. For example, stereological quantification of spinophilin-immunoreactive spines 79 and electron micrographic analyses of synapses have revealed that there is no age-related synapse loss in hippocampal area CA1 80 . Loss of CA1 synapses is characteristic of AD and, to a lesser extent, mild cognitive impairment in humans 81 .…”
Section: Synaptic Aging In the Hippocampusmentioning
confidence: 99%